Pemberian Tepung Kulit Pisang Terfermentasi Dalam Ransum Terhadap Persentase Karkas Ayam Kampung Kampung Super Umur 3 - 10 Minggu - Nyoman Handy Setiyawan; I Nyoman Kaca; Luh Suariani (Fakultas Pertanian, Universitas Warmadewa, 2022)
expensive. The cost of feed in a livestock business reaches 60-70% of the total production cost, so it is very important to find other alternatives in providing feed ingredients for rations. The feed ingredients that need to be used as alternative feed ingredients include those from agricultural industry waste, one of which is banana peels. The experimental design used was a completely randomized design (CRD) consisting of 5 treatments and 3 replications. The treatments were R0 (the ration without the addition of fermented banana peel flour), R1 (the ration containing 2.5% fermented banana peel flour.), R2 (the ration containing 5% fermented banana peel flour), R3 (the ration containing 7, 5% fermented banana peel flour), R4 (ration containing 10% fermented banana peel flour). The results showed that the addition of fermented banana peel flour in the ration did not have a significant effect (P>0.05) on all observed variables (cut weight, carcass weight, percentage of carcass and percentage of non-carcass). Giving fermented banana peel flour as much as 7.5% (R3) always absolute gave higher cutting weight and carcass weight results